Papan MUSI: Media Edukatif Interaktif untuk Meningkatkan Pemahaman KPK dan FPB Kelas V Sekolah Dasar - Ariella, Efa Larisa; Rahmadani, Salma Aulia; Susendra, M. Ari; Pratiwi , Ika Ari (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to develop educational media in the form of a MUSI (Multifunctional) board to improve students' understanding of the material of the Least Common Multiple (KPK) and Greatest Common Factor (FPB) in grade V elementary school. This research used the Research and Development (R&D) method with the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The research subjects were fifth grade students of SD 2 Demaan, and involved material experts and media experts for validation. The research instruments included expert validation sheets, student response questionnaires, and documentation. Data analysis used qualitative and quantitative approaches with a Likert scale. The validation results from material experts and media experts showed the level of media feasibility of 91% and 92% respectively with the category “very feasible”. The trial of students also showed a positive response with a feasibility score of 92%. The MUSI board media is designed in an interesting and interactive way to support students' active involvement in learning. The results showed that the use of this media can improve students' understanding of the concepts of KPK and FPB, as well as provide a fun and meaningful learning experience. Thus, the MUSI board media is recommended as an effective alternative mathematics learning media for use in elementary schools. The implication of this research shows that the MUSI Board media can improve the understanding of the KPK and FPB concepts through fun and interactive learning. This success opens up opportunities for the application of similar media in other mathematics materials to support a more effective learning process in elementary schools.